Advancement in graphene-based materials and their nacre inspired composites for armour applications—a review - Naveen, Jesuarockiam; Jawaid, Mohammad; Kheng, Lim Goh; Reddy, Degalhal Mallikarjuna; Muthukumar, Chandrasekar; Loganathan, Tamil Moli; Reshwanth, Koduri Naga Ganapathy Lakshmi (Multidisciplinary Digital Publishing Institute, 2021)
The development of armour systems with higher ballistic resistance and light weight has gained considerable attention as an increasing number of countries are recognising the need to build up advanced self-defence system to deter potential military conflicts and threats. Graphene is a two dimensional one-atom thick nanomaterial which possesses excellent tensile strength (130 GPa) and specific penetration energy (10 times higher than steel). It is also lightweight, tough and stiff and is expected to replace the current aramid fibre-based polymer composites. Currently, insights derived from the study of the nacre (natural armour system) are finding applications on the development of artificial nacre structures using graphene-based materials that can achieve high toughness and energy dissipation. The aim of this review is to discuss the potential of graphene-based nanomaterials with regard to the penetration energy, toughness and ballistic limit for personal body armour applications. This review addresses the cutting-edge research in the ballistic performance of graphene-based materials through theoretical, experimentation as well as simulations. The influence of fabrication techniques and interfacial interactions of graphene-based bioinspired polymer composites for ballistic application are also discussed. This review also covers the artificial nacre which is shown to exhibit superior mechanical and toughness behaviours.